Transatlantic homeland security : protecting society in the age of catastrophic terrorism - Dalgaard-Nielsen, Anja; Hamilton, Daniel S. (Daniel Sheldon), 1955- (Routledge, 2006)
This major new study presents both conceptual and practical guidance at a crucial time when intellectual and practical efforts to protect against the new terrorism should move beyond a purely domestic focus. Creating an effective and integrated national homeland security effort is a significant challenge. Europe and the United States have reacted differently to the emergence of mass casualty terrorism, but must work together to cope with the diverse issue areas, sectors, professions, and relevant actors involved in such a broad-based concept. The authors suggest that Europe and the US have a lo.